Use of Pulsed-Field Gel Electrophoresis for Molecular Epidemiologic and Population Genetic Studies of Mycobacterium tuberculosis - Singh, Samir P. (American Society for Microbiology, 1999)
Pulsed-field gel electrophoresis (PFGE) is a powerful molecular biology technique which has provided important insights into the epidemiology and population biology of many pathogens. However, few studies have used PFGE for the molecular epidemiology of Mycobacterium tuberculosis. A laboratory protocol was developed to determine the typeability, stability, and reproducibility of PFGE typing of M. tuberculosis. Formal data-analytical techniques were used to assess the genetic diversity elucidated by PFGE analyses using four separate restriction enzymes and by IS6110 RFLP analyses, as well as to assess the concordance among these typing methods. One hundred epidemiologically characterized clinical isolates of M. tuberculosis were genotyped with four different PFGE enzymes (AseI, DraI, SpeI, and XbaI), as well as by RFLP analysis with IS6110. Identical patterns were found among 34 isolates known to be genetically related, suggesting that the PFGE protocol is robust and reproducible. Among 66 isolates representing population-sampled cases, heterozygosity and information content dependency estimates indicate that all five genotyping systems capture quantitatively similar levels of genetic diversity. Nevertheless, comparisons between PFGE analyses and IS6110 typing reveals that PFGE provided more discrimination among isolates with fewer than five copies of IS6110 and less clustering in isolates with five or more copies. The comparisons confirm the hypothesis that the resolution of IS6110 RFLP genotyping is dependent upon the number of IS6110 elements in the genome of isolates. The general concordance among the results obtained with four independent enzymes suggests that M. tuberculosis is a clonal organism. The availability of a robust genotyping technique largely independent of repetitive elements has implications for the molecular epidemiology of M. tuberculosis.